Improving the Counting Early Competence of the Group B Students of PAUD An-Nisa Through Number Block Media - Fauziatul Halim; Muhammad Kharizmi; Syarifah Maihani (Edunesia: Jurnal Ilmiah Pendidikan, 2023)
This research is entitled “Improving The Counting Early Competence of The Group B Students of PAUD An-Nisa Through Number Block Media”. This research aims to know the improvement of the group B students' competence of PAUD An- Nisa in counting early by using number block media. In this research, the researcher used Action Research as the research Methodology, which consists of a plan, action, observation, and reflection. This research was done in 2 cycles, and the research instruments used were observation, scoring rubric sheets, and documentation. After implementing the research, the results showed that 1). the students’ competence in counting early using the number block media improved significantly. It can be proved by the result of students' learning result in cycle 1 showed 35% to be 89% in cycle 2. 2). Percentage of the student's activities in the first cycle was 50% increase to 94% in the second cycle. 3). The percentage of the teacher’s activities in cycle 1 was 65.41%, increasing to 96.5% in cycle 2. Based on the result above, using number block media could improve the competence of the group B students of PAUD An-Nisa in learning to count early. The number block media used could help the students learn to count early so that the student's competence could be improved.